Physicochemical and Rheological Characterization of Goat Whey - L.A.C, Freire; C.G, Pereira (Journal of Food Technology Research, 2018)
The whey is a product with high nutritional value, but it is too wasted. In this sense, this study aims to evaluate the physicochemical and rheological properties of goat whey. Content of total protein, lactose, fat, ash, total solids, humidity, pH and density of goat whey were determined. The whey rheological behavior was evaluated in different conditions of temperature and share rate. Two rheological models were used to fit the behavior of the goat whey and the activation energy was determined by Arrhenius equation. The characterization of goat whey showed satisfactory results. The increase in temperature resulted in a decrease of shear stress and apparent viscosity of goat whey, while the reverse was observed for strain rate increased. Ostwald-de-Waelle model presented a satisfactory arrangement with R² above 0.99 for all temperatures studied. The goat whey presented behavior index larger than 1, indicating that this is a dilatant fluid.